Evaluation of six leaf angle distribution functions in the Castillo® coffee variety (2017)
The study was conducted at the “Estacion Central Naranjal Cenicafe” (National Coffee Research Center, Chinchina, Caldas, Colombia) on Coffea arabica L. variety Castillo® to find the leaf angle distribution function that best described the tilt of the angles present in the canopy. Leaf angles were recorded for 1,559 leaves located in the upper, middle and lower profiles of the canopy. The observed leaf angle distribution was compared with the Beta, ellipsoidal and four de Wit distribution functions. The fit between comparisons was determined by the Pearson χ2 test and its significance, the regression coefficient statistically equal to one and the RMSE. Likewise, the leaf angle distribution recorded in the field per profile and their combination was described based on three angle classes (1st class: 0°-30°; 2nd class: 30°-60°; and 3rd class: 60°-90°) according to the Goudriaan criterion. Generally, the leaf angle distribution present in the canopy of Castillo® coffee variety is adequately described by the Beta function with two parameters and the ellipsoidal function based on the adjustment provided by the statistical tests.